Konsep Pendidikan Pesantren Modern Ummul Quro Al-Islami Banyusuci Kecamatan Leuwiliang Kabupaten Bogor - M Musfik Amrullah; Nanat Fatah Natsir; Muhammad Faqihudin (Jurnal Dirosah Islamiyah, 2020)
This research has a background which is about education in Indonesia. Where in Indonesia has a variety of educational institutions ranging from elementary school (elementary), junior high school (SMP), high school (high school), and tertiary education (PT). However, in reality, Indonesia has a unique educational institution and only exists in Indonesia, namely pesantren. The pesantren has various models and variations ranging from traditional pesantren (salafi) and modern pesantren (khalafi). The formulation of the problem of this research are (1) What is the concept of Modern Islamic Boarding School education of Ummul Quro Al-Islami Leuwiliang, Bogor? (2) how is the implementation of the modern Islamic boarding school concept of Ummul Quro Al-Islami Leuwiliang, Bogor? While the purpose of this study is (1) To know the educational concept of Modern Islamic Boarding School Ummul Quro Al-Islami Leuwiliang, Bogor. (2) Knowing how to implement the modern Islamic boarding school concept of Ummul Quro Al-Islami Leuwiliang, Bogor. In this study the authors use the type of library research or library research is research conducted using literature (literature) in the form of books, notes, or reports on the results of previous studies. In addition, this study also uses a qualitative approach. Where data is collected using the method of observation, interviews and documentation. The data analysis technique uses the Miles and Huberman analysis model which includes four interrelated components, namely data collection, data reduction, data presentation and drawing conclusions. From the results of this study it can be concluded that the Modern Islamic Boarding School Concept of Ummul Quro Al-Islami Leuwiliang, Bogor has three basic concepts, namely the government education curriculum, in this case the Ministry of Religion, salafi pesantren education, and Gontor pesantren education. Of the three curricula, the best is then combined, so that the new curriculum is integrated, which is the concept of the modern Islamic boarding school Umm al-Quro Al-Islami. Key Word: Concept, Islamic Boarding School, Islamic Education.